1995
DOI: 10.3168/jds.s0022-0302(95)76657-7
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Potentially Pathogenic Bacteria in Swiss Hard and Semihard Cheeses Made from Raw Milk

Abstract: This study examined the ability of potentially pathogenic bacteria to grow and to survive during the manufacture and ripening of Swiss hard and semihard cheese varieties made from raw milk. The results show that hard cheeses are hygienically safe; 1 wk after fabrication, the inoculated pathogens (Aeromonas hydrophila. Campylobacter jejuni, Escherichia coli, Listeria monocytogenes, Pseudomonas aeruginosa, Salmonella spp., Staphylococcus aureus, and Yersinia enterocolitica) could no longer be detected. At the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 18 publications
4
42
0
Order By: Relevance
“…There is already supporting evidence that the consumption of some cheese products (curd and cottage cheese) is lower in individuals infected with campylobacter than in controls 20 , with ORs similar to those found in the present study. When cheese is inoculated with pathogens (including campylobacter) their survival times are short 21 , suggesting the presence of bactericidal components. Cheese and other food items that were eaten more often by controls have a relatively high fat content.…”
Section: Discussionmentioning
confidence: 99%
“…There is already supporting evidence that the consumption of some cheese products (curd and cottage cheese) is lower in individuals infected with campylobacter than in controls 20 , with ORs similar to those found in the present study. When cheese is inoculated with pathogens (including campylobacter) their survival times are short 21 , suggesting the presence of bactericidal components. Cheese and other food items that were eaten more often by controls have a relatively high fat content.…”
Section: Discussionmentioning
confidence: 99%
“…This source was not included here because a genotyping study from Switzerland suggested that isolates likely to originate Risk attribution of Campylobacterfrom cattle accounted for <10% [48]. Meat from ruminants and raw milk cheese is generally considered to be of low risk [49,50] and raw milk is only rarely consumed in Switzerland. However, occupational and environmental exposure pathways for ruminants might be relevant and should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…aureus and, in some cases, production of enterotoxins during manufacture and ripening in most common cheese varieties, have been thoroughly investigated by several researchers because of the sanitary significance (Van Schouwenberg-Van Focken et al 1979;Gomez-Lucia et al 1992;Barbosa et al 1993a;Barbosa et al 1993b;Otero et al 1993;Anunciacao et al 1994;Bachmann and Spahr 1995). The results obtained have varied depending on many factors including cheese type, and nature and activity of the starter culture used.…”
Section: Introductionmentioning
confidence: 99%